Down-regulation of cathepsin S and matrix metalloproteinase-9 via Src, a non-receptor tyrosine kinase, suppresses triple-negative breast cancer growth and metastasis - Gautam, Jaya; Banskota, Suhrid; Lee, Hyunji; Lee, Yu-Jeong; Jeon, Yong Hyun; Kim, Jung-Ae; Jeong, Byeong-Seon (Experimental & molecular medicine, 2018)
Triple-negative breast cancer (TNBC) is a highly metastatic breast cancer with poor prognosis. In the present study, we demonstrated that Src, a non-receptor tyrosine kinase, might provide an effective therapeutic strategy to overcome TNBC invasion and metastasis, which are mediated via the synergistic action of the lysosomal enzyme cathepsin S (CTSS) and gelatinase MMP-9. Knock-down of MMP-9 and CTSS using siRNAs resulted in a synergistic suppression of MDA-MB-231 cell invasion, which was similarly observed with pharmacological inhibitors. During the screening of new drug candidates that suppress both CTSS and MMP-9, BJ-2302, a novel 7-azaindolin-2-one derivative, was discovered. Src, an upstream activator of both pathways (PI3K/Akt and Ras/Raf/ERK) responsible for the expression of CTSS and MMP-9, was identified as a high-affinity target of BJ-2302 (IC 90 : 3.23 µM) through a Src kinase assay and a drug affinity responsive target stability (DARTS) assay. BJ-2302 effectively suppressed MDA-MB-231 cell invasion (Matrigel invasion assay) and metastasis (chorioallantoic membrane assay xenografted with MDA-MB-231-luc2-tdTomato cancer cells). Unlike Z-FL-COCHO (potent CTSS inhibitor), BJ-2302 did not induce any cytotoxicity in MCF-10A normal breast epithelial cells. Additionally, BJ-2302 (1 mg/kg) strongly suppressed TNBC cell proliferation in vitro and tumor growth in a xenograft mouse tumor model. The anti-metastatic and anti-tumor effects of BJ-2302 were superior to those of Z-FL-COCHO (1 mg/kg) or batimastat (30 mg/kg), a pan-MMP inhibitor. In summary, inhibition of Src kinase suppressed TNBC tumor growth and metastasis, and Src inhibitors such as BJ-2302 may constitute a novel therapeutic tool to treat breast cancer that expresses high levels of CTSS and MMP-9. Breast cancer: Trapping tumors in place Drugs that inhibit two protein-digesting enzymes could offer potent protection against tumor growth and metastasis in an aggressive form of breast cancer. “Triple-negative breast cancer” (TNBC), which lacks three common tumor biomarkers, carries a poor prognosis for patients, with few treatment options. Enzymes that degrade the protein matrix that anchors tumor cells play a prominent role in metastasis. Researchers led by Jung Ae Kim and Byeong-Seon Jeong at Yeungnam University, Gyeongsan, South Korea, have demonstrated that these enzymes offer potential therapeutic exploitation. The researchers identified a compound that simultaneously suppresses the activity of two different matrix-digesting enzymes. This parallel inhibition markedly reduced tumor growth and metastatic invasion in mouse models of TNBC, with minimal toxicity to non-cancerous cells. This approach could thus offer new hope for treating a challenging class of tumors.